Rapidly Progressive Erosive Arthritis: A Case of Multicentric Reticulohistiocytosis Emphasizing Radiographic Progression, Ultrasound Features, and Efficacious Treatment - David DeMasters; Seth VanDerVeer; Kyle Maier; Hamish Patel (Annals of Internal Medicine: Clinical Cases)
We present a case of multicentric reticulohistiocytosis (MRH) in an African American man with both axial and peripheral articular involvement in the absence of typical cutaneous features. Spinal involvement is ill-defined in MRH. This case illustrates spinal lesions as well as the aggressive joint destruction, bony fragmentation, and inflammatory changes through a series of radiographs of the hand and musculoskeletal ultrasound images. Combination therapy with corticosteroids, methotrexate, adalimumab, and zoledronic acid was effective and led to marked clinical improvement.